PENERAPAN PENDEKATAN SAINTIFIK MELALUI MODEL PROBLEM SOLVING UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR FISIKA DI KELAS X IPA.1 SMAN 9 KOTA BENGKULU - Zulfia Muslimawati; Rosane Medriati; Eko Risdianto (Kumparan Fisika, 2017)
This study is a classroom action research conducted in four cycles aims to describe the increase of student learning activities, student learning motivation and student learning outcomes on business and energy concepts. Subjects in this study were students of class X IPA 1 which amounted to 29 people consisting of 14 male students and 15 female students. Results of student activity on cycle I with average score of 20 in active enough category, cycle II of 23 in active enough category, cycle III of 28 in active category, and IV cycle of 29,5 in active category. The result of questionnaire of students' learning motivation in cycle I with average score of 44,48 in medium category, cycle II equal to 51,74 in medium category, cycle III equal to 57,31 in high category, IV cycle equal to 63,86 in high category. Students' learning outcomes of knowledge aspects in the first cycle obtained 70,86% absorption and learning completeness of 37,93% (not completed), cycle II obtained 76,72% absorption and learning completeness of 79,31% (thorough), cycle III absorption of 82,24% And learning completeness 89,66% (complete) and cycle IV absorption of 93,97% and complete learning 100% (thorough). Based on the results of research can be concluded that the application of scientific approach through Problem Solving model can improve student learning activities, student learning motivation and student learning outcomes.Keywords: Scientific Approach, Problem Solving Model, Student Learning Activity, Student Learning Motivation and Student Learning Outcomes